When poetry ruled the streets : the French May events of 1968 - Feenberg, Andrew (State University of New York Press, 2001)
"More than a history, this book is a passionate reliving of the French May Events of 1968. The authors, ardent participants in the movement in Paris, documented the unfolding events as they pelted the police and ran from the tear gas grenades. Their account is imbued with the impassioned efforts of the students to ignite political awareness throughout society. Feenberg and Freedman select documents, graffiti, brochures, and posters from the movement and use them as testaments to a very different and exciting time. Their commentary, informed by the subsequent development of French culture and politics, offers useful background information and historical context for what may be the last great revolutionary challenge to the capitalist system."--Jacket